Étude Écocritique De En Compagnie Des Hommes De Veronique Tadjo - Sallah, C.A. (Collection Recherches & Regards D’afrique, 2023)
Nature and environment are two major entities which influence human lives, but the import of their influence depend on the relationship men establish between themselves and their constituent elements such as earth, trees, animals and water bodies. As a result, literary critics develop ecocriticism in order to establish a legitimate relationship between men and their environment. In In the Company of Men, Véronicque Tadjo tries to establish the relationship that exists between Africans and nature and the repercussions of their activities on the environment. Human activities 109 ISBN : 978-2- 493659- 04- 0 COLLECTION RECHERCHES & REGARDS D’AFRIQUE VOL 2 N 0 4 / JUIN 2023 provokes characters like the Baobab, Bat and Ebola to lament about African’s behaviour toward the environment. Our study therefore aims at studying, by means of ecocriticism, the relationship between human being and nature, the connection between men and the environment, the causes of lamentation by natural entities about men and their reciprocal reactions against mankind.
Research Article
Keywords: nature ecocriticism environment man relation